Molecular dynamics of reactions between (4, 0) zigzag carbon nanotube and hydrogen peroxide under extreme conditions. (19th March 2018) - Disrud, Brendon; Han, Yulun; Gifford, Brendan J.; Kilin, Dmitri S.
ABSTRACT: Single-wall carbon nanotubes (CNTs) have been suggested as potential materials for use in next-generation gas sensors. The sidewall functionalisation of CNTs facilitates gas molecule adsorption. In this study, density functional theory (DFT)-based ab initio molecular dynamics simulations are performed for a periodic zigzag single-wall (4, 0) CNT surrounded by a monolayer of hydrogen peroxide molecules in an attempt to find conditions that favour sidewall functionalisation. The dependency of dynamics on charge states of the system is examined. It is found negative charges favour reactions that result in the functionalisation of the CNT. First principles molecular dynamics of defect formation yields chemically reasonable structure of stable defects, which can be reproduced in CNTs of any diameter and chirality. The explored hydroxyl and hydroperoxyl defects increase conductivity in a large diameter (10, 0) CNT, while decrease conductivities in a small diameter (4, 0) CNT. Abstract :